2020
DOI: 10.1002/aoc.5541
|View full text |Cite
|
Sign up to set email alerts
|

Fast recovery of Au (III) and Ag(I) via amine‐modified zeolitic imidazolate framework‐8

Abstract: In this paper, zeolitic imidazolate framework‐8 modified by the ethanediamine (NH2‐ZIF‐8) was employed for adsorbing Au (III) and Ag(I) from aqueous solutions. The adsorption capacities of NH2‐ZIF‐8 towards Au (III) and Ag(I) were found to be significantly affected by the pH values of the solution. The adsorption kinetics studies show that NH2‐ZIF‐8 presents a fast adsorption property towards metals, attaining 93% of adsorption equilibrium uptake for Au (III) within the first 30 min. This phenomenon can be asc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 35 publications
(31 reference statements)
1
13
0
Order By: Relevance
“…CS/PmPD membranes can process up to 410 mg g −1 of Au( iii ), which is comparable to previously reported values (Table S1, ESI†). 10,12,25–40…”
Section: Resultsmentioning
confidence: 99%
“…CS/PmPD membranes can process up to 410 mg g −1 of Au( iii ), which is comparable to previously reported values (Table S1, ESI†). 10,12,25–40…”
Section: Resultsmentioning
confidence: 99%
“…Yuan et al used UiO-66-Schiff to recover Co­(II) with high selectivity in a mixed solution containing Na + , K + , Mg 2+ , Ca 2+ , Co 2+ , and Ni 2+ . Zhou et al utilized NH 2 -ZIF-8 for selectively adsorbing Ag­(I) in a mixture of Ag­(I), Ni­(II), Cd­(II), and Zn­(II) . The above-mentioned research indicated that MOFs exhibited huge potential in metal ion adsorption due to controllable chemical functionality .…”
Section: Introductionmentioning
confidence: 99%
“…30 Zhou et al utilized NH 2 -ZIF-8 for selectively adsorbing Ag(I) in a mixture of Ag(I), Ni(II), Cd(II), and Zn(II). 31 The above-mentioned research indicated that MOFs exhibited huge potential in metal ion adsorption due to controllable chemical functionality. 32 Unfortunately, as far as we know, the related study of MOFs focusing on absorbing Au at low concentration in complex solutions has rarely been reported (Figure 1).…”
Section: ■ Introductionmentioning
confidence: 99%
“…1 Poisonous heavy metal ions can cause serious diseases such as Minamata disease 2 ;t h e r e f o r e ,p r ocesses for the treatment and removal of these ions are well established. [3][4][5][6][7] However, the capture and recycling of essential nutrient metal ions have been studied to a limited extent, despite their critical roleinthefunctioningofthehumanbody.…”
Section: Introductionmentioning
confidence: 99%